135°
Объяснение:
тр.АКС
АК=АС (условие) => тр.АКС - р/б => уг.АКС=уг.АСК
тр.ВМС
ВМ=ВС (условие) => тр.ВМС - р/б => уг.ВСМ=уг.ВМС
тр.АВС
Пусть уг.АКС=у. Тогда:
уг.АКС=уг.АСК=у
уг.ВАС=уг.АКС+уг.АСК=2у, т.к. уг.ВАС - внешн. угол треуг. АКС.
Пусть уг.ВМС=х. Тогда;
уг.ВМС=уг.ВСМ=х
уг.АВС=уг.ВМС+уг.ВСМ=2х, т.к. уг.АВС - внешн. угол треуг. ВМС.
тр.АВС - п/у.
уг.АВС+уг.ВАС=90°
2х+2у=90°
х+у=45°
тр.МСК
уг.МСК=уг.АСК+уг.АСВ+уг.ВСМ=х+90°+у=45°+90°=135°
135°
Объяснение:
тр.АКС
АК=АС (условие) => тр.АКС - р/б => уг.АКС=уг.АСК
тр.ВМС
ВМ=ВС (условие) => тр.ВМС - р/б => уг.ВСМ=уг.ВМС
тр.АВС
Пусть уг.АКС=у. Тогда:
уг.АКС=уг.АСК=у
уг.ВАС=уг.АКС+уг.АСК=2у, т.к. уг.ВАС - внешн. угол треуг. АКС.
Пусть уг.ВМС=х. Тогда;
уг.ВМС=уг.ВСМ=х
уг.АВС=уг.ВМС+уг.ВСМ=2х, т.к. уг.АВС - внешн. угол треуг. ВМС.
тр.АВС - п/у.
уг.АВС+уг.ВАС=90°
2х+2у=90°
х+у=45°
тр.МСК
уг.МСК=уг.АСК+уг.АСВ+уг.ВСМ=х+90°+у=45°+90°=135°